KONSEP DASAR AKUNTANSI SEBAGAI LANDASAN PENYUSUNAN LAPORAN KEUANGAN: KAJIAN PUSTAKA TENTANG PRINSIP ENTITAS, AKRUAL, KESINAMBUNGAN USAHA, DAN HARGA PEROLEHAN - Gunawan Widjaja (Berajah Journal, 2026)
This article examines the fundamental concepts of accounting as the basis for the preparation of financial statements through a literature review of four key principles: the entity principle, the accrual basis, the going concern assumption, and the historical cost principle. The entity principle emphasises the separation between the business entity and its owners, ensuring that financial statements objectively reflect the company’s financial position. The accrual basis ensures that revenue and expenses are recognised in the period in which they occur, rather than when cash is received or paid, thereby making financial performance more relevant and comparable. The going concern assumption allows for the measurement of assets and liabilities under normal conditions, including the use of periodic depreciation, whilst the historical cost principle provides an objective and verifiable basis for the measurement of assets and liabilities. The findings of the study indicate that the four fundamental accounting concepts are interrelated and form a crucial foundation for maintaining the consistency, reliability, and relevance of financial statement information for users.